Factors Affecting the Selection of Risky Financial Assets in Chinese Households: Empirical Research Based on the data of China Household Finance Survey - Deng, Weihua (2018)
Using the cross-sectional data from CHFS in 2013, we conduct an empirical analysis of the factors affecting the participation and its depth in the risky financial markets of Chinese households. The analysis is based on three theories, namely the life-cycle investment theory, the modern portfolio theory and the background risk theory. Except for risky financial assets of Chinese households, we also select the most representative risky financial asset in the portfolio structure of the Chinese households, stock assets, as the research subject after an analysis of the status quo of Chinese household financial assets. In order to study the factors that have effects on participation and its depth in the risky financial markets of Chinese households, we establish the Probit regression model and the Tobit regression model. This paper analyzes the influence of factors from three aspects, namely, characteristics of the head in the household, household characteristics and regional characteristics. The empirical results show that there is a significant life-cycle effect in Chinese household's selection of risky financial assets. Male heads of the household prefer secure financial assets. The improvement of education level and the improvement of health status help Chinese households actively hold risky financial assets while risk aversion has a negative effect on them. Moreover, an increase in total household income will encourage Chinese households to enter risky financial markets and hold more risky financial assets. However, when the households are from rural area in China, they are not willing to enter the risky financial market or hold risky financial assets. Finally, based on the conclusions of this paper, we make recommendations to the Chinese government and Chinese households and discuss the shortcomings of this paper.